Peran Audit Committee Sebagai Pemoderasi Antara Tax Management Policy Dan Intencity Capital Terhadap Earnings Management Practices Pada Saat Pandemik Covid-19 - Pangestu, Juan Carlos; Rusli, Yohanes Mardinata; Margaretha, Phebyana (JURNAL ADMINISTRASI KANTOR; Vol 10 No 1 (2022): Jurnal Administrasi Kantor (Juni 2022)DO - 10.51211/jak.v10i1.1801, 2022)
The company's profit is one component that is considered by management to determine the company's financial health condition. The practice of earnings management is carried out by the company to maintain the health of the company so that stakeholders are not worried about the sustainability of the company. This study examines the role of the audit committee as a moderator between tax management and capital intensity on lab management practices during the Covid-19 pandemic. The sample is taken from financial reports on the Indonesia Stock Exchange in 2017 â€“ 2019 for manufacturing companies in the consumer goods sector. The method of analysis uses multiple linear analysis with SPSS 25. This study results that earnings management practices are influenced by tax management but are not influenced by Capital Itencity. The audit committee as a moderator gives an influence between tax management and earnings management practices, while this does not affect Capital Itencity on earnings management practices in the company.   Keywords : Tax Management, Audit Committee, Earnings Management Practices